Factors Affecting the Context for Motivation in Public Organizations - Perry, James L.; Porter, Lyman W. (Academy of Management Review, 1982)
A comparative framework is used to assess the present understanding of the motivational context in public organizations. Comparative public-private research on individual, job, work environment, and external variables affecting motivation is reviewed. In light of this research, the efficacy of four motivational techniques—monetary incentives, goal setting, job design, and participation—is discussed. An agenda is offered for future research, focusing on topics such as the measurability of performance, goal clarity, and job security.